LAMP Coupled CRISPR-Cas12a Module for Rapid, Sensitive and Visual Detection of Porcine Circovirus 2 - Lei Lei; Fan Liao; Lei Tan; Deyong Duan; Yang Zhan; Naidong Wang; Yuge Wang; Xiaoye Peng; Kaixin Wang; Xiaojiu Huang; Yi Yang; Aibing Wang (Animals, 2022)
Porcine circovirus 2 (PCV2) is the main pathogen of porcine circovirus-associated disease (PCVAD), which can cause considerable economic loss to the pig industry. The diagnosis of PCVAD is complicated and requires a series of clinical, pathological, and virological methods. Therefore, a rapid, highly sensitive, on-site, and visual diagnostic approach would facilitate dealing with the spread of PCV2. In this study, we intended to establish a new and effective PCV2 detection method through combining the no specific equipment requirement advantage of loop-mediated isothermal amplification (LAMP) with the property of clustered regular interspaced short palindromic repeats (CRISPR)/Cas12a system possessing the huLbCas12a collateral cleavage activity able to cleave single-stranded DNA fluorophore quencher probe sensor (designed as LAPM-CRISPR). Following a series of optimizations of its reaction conditions, this LAMP-CRISPR-based PCV2 detection could be conducted in constant temperature equipment, with the result reflected in a direct visual readout way. This established PCV2 detection approach presented fine sensitivity, rapidity, specificity, and reliability, as demonstrated by a low detectable limit of 1 copy/μL, completed within an hour, no cross-reaction with main porcine DNA or RNA viruses like PCV1, PCV3, and PEDV, and a 100% coincidence rate with that of the quantitative PCR (qPCR) method in the evaluation of 30 clinical blood samples, respectively. Therefore, this novel method makes rapid, on-site, visual, highly sensitive, and specific detection of PCV2 possible, facilitating the prevention of this pathogen in the field.